Odnos mladih odraslih do ustvarjanja družine in rojevanja - Kuhar, Metka (IB revija (Ljubljana), 2007)
This article looks into the circumstances surrounding the starting of young adults' family and childbearing in Slovenia. It examines the demographic and family trends, structural factors that play an important role in family formation (e.g. labour market, housing situation, gender roles), and the findings of quantitative and qualitative surveys on transitions to family life among young adults in Slovenia. The quantitative data indicate high aspirations of young adults for family life and children. The qualitative data show that subjective rather than objective factors are a key "barrier" to family formation
Keywords: Mladi odrasli; Young adults; Družina; Family; Births; Rojstva; mladi; rodnost; starševstvo; raziskave; Slovenia; Slovenija